PORTRAYAL OF WOMAN IN THE CAVE PAINTINGS OF AJANTA - Tripathi, Shubha; Jain, Beena (International Journal of Research -GRANTHAALAYAH, 2019)
The thirty rock cut cave temples of Ajanta located near a village named “Ajistha” in Aurangabad district of Maharashtra state. The caves are carved in a half crescent shape overlooking the Waghora river. The caves are located at a picturesque location having beautiful natural surroundings. Because of this peace and godly environment Buddhist monks might have chosen this place for their artistic endeavour. The caves possess well carved sculptures, pillars, entrances and walls are embellished with beautiful paintings. The art of Ajanta flourished from 1st century BC to 7th century AD. The Ajanta art is considered as the classical age of Indian painting. The artists of Ajanta did not follow the law of perspective and represented the figures in its entirety rather than appeared through a normal eye. Ajanta artists tried to depict the whole view through horizontal bands. In the paintings at Ajanta, the background was painted at the topmost band, the middle part of the painting below it and the foreground below the middle ground.